Determinants of Liquidity Ratio and Profitability Ratio: Analysis Before IPO and After IPO (Financial Management Review Literature) - Harry Pambudi (Dinasti International Journal of Education Management And Social Science, 2022)
Literature article Reviewing Determinants of Liquidity Ratios and Company Profitability Ratios related to the influence of Pre-IPO Conditions and Post-IPO Conditions is a scientific article to formulate research hypotheses on the influence of variables in subsequent research, within the scope of Financial Management. Writing this Literature Review article uses the library research method, sourced from Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) The Effect of Company Conditions Before IPO on its Liquidity Ratio; 2) The Influence of the Company's Condition After the IPO on its Liquidity Ratio; 3) Influence of Company Conditions Before IPO on Profitability Ratios; 4) The Influence of Company Conditions After IPO on Profitability Ratios; and 5) Analysis of the Effect of Liquidity Ratios on Company Profitability Ratios. Apart from these 2 exogenous variables that affect the endogenous variable Liquidity Ratio and Profitability Ratio, things that can also be other factors are Sales Growth, Earning per Share (EPS) variables, and Ownership Structure.